Multifunctionality of agricultural activities, changing rural identities and new institutional arrangements. (26th August 2008) - Renting, Henk; Oostindie, Henk; Laurent, Catherine; Brunori, Gianluca; Barjolle, Dominique; Jervell, Anne; Granberg, Leo; Heinonen, Maarit
This paper builds on the outcomes of a state-of-the-art review of research for the European research project MULTAGRI, with a particular focus on the conceptualisation of Multifunctional Agriculture (MFA) from a 'supply side' perspective. It argues that a consistent and satisfactory conceptual framework for studying the supply of MFA at farm and territorial level is still largely lacking and that, when consistently applied, the recognition of the multifunctionality of agriculture fundamentally challenges the ways in which agricultural activities are observed, analysed and their effects assessed. This is elaborated by discussing five 'critical questions' for studying the supply of MFA: (1) what are relevant functions of agriculture? (2) how to define agricultural activities? (3) how to identify relevant farm/firm categories? (4) how to study the role of changing rural identities? and (5) what is the role of new territorial and institutional arrangements?